2007
DOI: 10.3164/jcbn.2007028
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Trace Elements in Patients with Crohn’s Disease Receiving Enteral Nutrition

Abstract: Summary We investigated the trace element status in Crohn's disease (CD) patients receiving enteral nutrition, and evaluated the effects of trace element-rich supplementation. Thirty-one patients with CD were enrolled in this study. All patients were placed on an enteral nutrition regimen with Elental ® (Ajinomoto pharmaceutical. Ltd., Tokyo, Japan). Serum selenium, zinc and copper concentrations were determined by atomic absorption spectroscopy. Serum selenoprotein P levels were determined by an ELISA system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Our observation that selenium levels were higher in healthy individuals than in diseased patients confirms the epidemiological data that Se deficiency may make one susceptible to the disease [28,29]. However, further studies are needed in order to explore whether decreased Se levels have developed actually in consequence of the inflammatory process, as Se levels may decrease also secondarily in chronic diseases associated with a release of free radicals [4,16]. The exact mechanism of the beneficial effect exerted by Se on the immune system has not yet been explored by the research up to now, but its inhibitory effect on the formation of autoantibodies may be doubtless beneficial in the treatment of AT.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our observation that selenium levels were higher in healthy individuals than in diseased patients confirms the epidemiological data that Se deficiency may make one susceptible to the disease [28,29]. However, further studies are needed in order to explore whether decreased Se levels have developed actually in consequence of the inflammatory process, as Se levels may decrease also secondarily in chronic diseases associated with a release of free radicals [4,16]. The exact mechanism of the beneficial effect exerted by Se on the immune system has not yet been explored by the research up to now, but its inhibitory effect on the formation of autoantibodies may be doubtless beneficial in the treatment of AT.…”
Section: Discussionsupporting
confidence: 74%
“…Serum Se levels were determined by atomic absorption method (Zeemann 4100 ZL, Germany) in patients and in 20 healthy individuals (18 were female; mean age: 40.1 ! 8.3 years) whose results of thyroid function were in the physiological range and who had no elevated antibody titres [16,21,22]. During the study we administered a food supplement product that was given permission by the local Ethical Committee in accordance to the requirements of Helsinki Declaration.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elental ® (EA Pharma Co., Ltd., Tokyo, Japan), an elemental diet (ED) with L-glutamine which has an easily digestible nutrition formula that combines amino acids, carbohydrates, vitamins, minerals and with minimal fat content has been used in Japan as a treatment for malnourished patients (22,23). Elental ® has been reported to be useful in the treatment of Crohn's disease (24)(25)(26)(27), as well as in the management of chemotherapy-induced mucositis in cancer patients (28,29). We have been using Elental ® for the treatment of malnutrition in patients undergoing chemotherapy and/or radiotherapy in our hospital since 2011, and our clinical study revealed the efficacy of Elental ® in ameliorating chemotherapy-induced oral mucositis and dermatitis in head and neck cancer patients (30).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they found low serum Se level in CD patients against controls (55). In a study done by Tomoko Johtatsu et al serum Se level was found to be significantly lower in CD patients compared to the control group (56). Involvement of selenium in antioxidant system has been reported yet its role in modulating oxidative stress and preventing chronic diseases is controversial (57).…”
Section: Discussionmentioning
confidence: 99%